Assessment of Nurses’ Knowledge About Aggression and Ways Used for Aggressive Patients at Psychiatric Wards - Abdulla, Mohammed; Mohammed, Saja Hashem . (International Journal of Psychosocial Rehabilitation, 2020)
Background: The media gives a great deal of attention to persons with mental illness who commit an aggressive act. Violence and aggression in healthcare is prevalent and often highlighted by the media, researchers and healthcare organizations as well as by healthcare professionals . Incidents of violence and/or aggression are hard and perilous clinical problems that can potentially lead to harm to both staff and patients. The high prevalence of aggression will increase the adverse consequences and highlights the importance of effective medical treatment for aggressive patients.Objectives: To evaluate nurses’ knowledge regarding aggression and ways used for aggressive patients at Psychiatric Hospital in Baghdad.Materials and Method: A descriptive study was conducted for the period from 9 July 2019 to 18 July 2019 .A probability sampling (random technique) was used, the sample consisted of (50) nurses who were working at Psychiatric Training Hospital in Baghdad .Data were collected by using constructed questionnaire after validity and reliability of it were estimated. Reliability of the questionnaire was estimated through a pilot study and the validity was submitted through (14) experts related in the field of study. All data were collected through an interview approach. Data were analyzed throughout using of descriptive and inferential statistical analysis test using SPSS Version-26.Results: The findings of current study indicate that the nurses have intermediate level of knowledge regarding aggression and ways used for aggressive patients.Conclusion: The study concludes that there is a considerable lack in nurses’ knowledge regarding approaches utilizing to deal with aggressive psychiatric patient.Recommendations: The study recommends that there is an important need for education and training the nurses who have work in psychiatric ward especially who have lack or inadequate knowledge and skills about the ways to deal with psychiatric patients .